The village woman in Peasant Memories from the 1930's - Pawłowska, Kinga (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
The paper is devoted to the attempt at reconstructing the cosmology of the author of the memories described in the Peasant Memories from the 1930’s. The inspiration was taken from accomplished historians who belong to a new cultural history and who are interested in culture and aspects of everyday life, mentality and daily issues of the people who lived in the past.The tools of social sciences and humanities offer abundant resources for the possible theoretical conceptions taken from this material to be analysed. It appears tat an appropriate tool which can be used to analyse these collected memories is the grid/group theory of Mary Douglas, completed by other authors, including Pierre Bourdieu and Chris Schilling. The most important concepts of Mary Douglas’s theory are the social context, grid, group and cosmology. The main idea involves tracing the ways in which some cosmologies are produced in specific conditions and the possibility to describe them with the use of such variables as grid and group social contexts. All of these concepts have been briefly discussed in this article. The analyses conducted indicates that the village woman cosmology could be ascribed to the segment C of the pattern, characterized by a strong grid and a strong group. In the conditions of the strong group, the group thoroughly controls individual lives and in the condition of strong grid, there are some precisely described social roles. In the women's narration it is easy to see, as apparent otherwise in social sciences, a strain between the community and an individual. A strain that could have some dramatic consequences.
Keywords: the village woman; peasants’ memories; new cultural history; grid/group conception; cosmology